Informal Pew-Renting and Pew-Openers in English Anglican Churches. - Bennett, J.C. (Church History & Religious Culture, 2020)
As opposed to formal pew-renting, which characterised less affluent Anglican churches in England, wealthier churches often used informal pew-renting. In this form, congregants were expected to "tip" pew-openers—themselves generally from the working class—a sixpence, shilling or half-a-crown, to obtain favourable seating for a single service. But the "tips" were actually bribes, and according to popular descriptions, pew-openers frequently relegated those financially unable to "tip" to much less desirable seating. Over the centuries the English clergy has endured many insulting and coarse epithets, such as calling a chicken's backside "the parson's nose" and referring to urination as "shaking hands with the vicar." But no role has historically engendered so much constant suspicion and hatred as has the pew-opener. This article investigates the role of the pew-opener and the surrounding controversy, and the churches' response to pew-openers' behavior.